“Bernardino Ramazzini, three hundred years after his death”, Padua (Italy), October 18th, 2014 - Riva, Michele Augusto; Zampieri, Fabio (La Medicina del Lavoro, 2015)
The year 2014 has marked the tercentenary from the death of Bernardino Ramazzini (1633-1714), universally credited as the founder of Occupational Health (5, 9, 10, 11). Indeed, the renowned physician died on November 5th 1714 in Padua, where he had been appointed as Professor of Practical Medicine at the local prestigious University from the year 1700. To commemorate this anniversary, the professors of Occupational Health of the University of Padua, the Italian Society of Occupational Health and Industrial Hygiene (Società Italiana di Medicina del Lavoro eIgiene Industriale, SIMLII), the International Commission on Occupational Health (ICOH) and the University of Padua organized a conference in the wonderful location of Palazzo Bo (Main Hall) under the patronage of the Padua Municipality, the Workers’ Compensation Authority (INAIL), the Venetian Region and the Societas Internationalis Historiae Medicinae.[...]